Where do sexually active female London students go to access healthcare? Evidence from the POPI (Prevention of Pelvic Infection) chlamydia screening trial. Issue 5 (13th March 2012) - Green, Ruth; Kerry, Sarah R; Reid, Fiona; Hay, Phillip E; Kerry, Sally M; Aghaizu, Adamma; Oakeshott, Pippa
Abstract : Background: Little is known about where sexually active female students access healthcare. Objectives: Using data from the Prevention of Pelvic Infection (POPI) cohort, the authors aimed to: Describe where sexually active female students aged ≤27 years reported accessing healthcare. Investigate the association between numbers of sexual partners during 12 months of follow-up and healthcare usage, health-related quality of life (EQ-5D) and demographic and behavioural characteristics. Methods: Participants provided vaginal swabs and completed questionnaires on sexual health and quality of life at baseline and at a 12-month follow-up. The follow-up questionnaire also asked about healthcare attendances during the previous 12 months. Mann–Whitney tests were used to relate healthcare seeking behaviour and other characteristics to reported numbers of partners during follow-up. Results: Of 1865 women included in the analysis, 79% paid at least one visit to their general practice during follow-up, 23% attended an accident and emergency/walk-in clinic, 21% a family planning clinic and 14% a genitourinary medicine clinic. As the number of sexual partners increased (0–1, 2–3, 4+), women were more likely to have visited a genitourinary medicine clinic (10%, 16%, 30%, p<0.001) or accident and emergency/walk-in clinic (21%, 26%, 29%, p<0.002). Women with more sexual partners were also more likely to smoke, use condoms, be aged <16 years at sexual debut, have bacterial vaginosis, chlamydia or gonorrhoea at baseline and to have lower EQ5-D scores. Conclusion: This is the first UK study of healthcare attendance in multiethnic female students recruited outside healthcare settings. The high attendance in general practice may represent a valuable opportunity for screening for sexually transmitted infections.